Should Angiotensin-Converting Enzyme Inhibitors ever Be Used for the Management of Hypertension? - Turner, Jeffrey M. (Curr Cardiol Rep, 2020)
PURPOSE OF REVIEW: Angiotensin-converting enzyme inhibitors and angiotensin receptor blockers are commonly used anti-hypertensive medications in a number of clinical settings. They are often used interchangeably, but we pose the provocative question as to whether they should be. We review the literature to evaluate for any differences in efficacy between the two classes in order to determine if the greater side effects associated with angiotensin-converting enzyme inhibitors are offset by any advantageous effects on outcomes to warrant their use over angiotensin receptor blockers. RECENT FINDINGS: In many clinical scenarios, the data supports similar efficacy between ACE inhibitors and ARBs, while in a minority of others, there are murky signals from previous trials that suggest ACE inhibitors may be better. However, when reviewing the literature in its entirety, and taking into account recently published pooled analysis and head to head trials, it is reasonable to conclude that ACE inhibitors and ARBs have similar efficacy. This is in contrast to data on adverse effects, which consistently favors the use of ARBs. SUMMARY: From the available data, it is reasonable to conclude that ACE inhibitors and ARBs have equal efficacy yet unequal adverse effects. It is in this context that we take the provocative stance that ACE inhibitors should not be used to treat hypertension.